2013
DOI: 10.1371/journal.pone.0070478
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Nasopharyngeal Carriage and Antibiotic Resistance of Respiratory Bacteria in Indigenous Australian and Alaska Native Children with Bronchiectasis

Abstract: BackgroundIndigenous children in Australia and Alaska have very high rates of chronic suppurative lung disease (CSLD)/bronchiectasis. Antibiotics, including frequent or long-term azithromycin in Australia and short-term beta-lactam therapy in both countries, are often prescribed to treat these patients. In the Bronchiectasis Observational Study we examined over several years the nasopharyngeal carriage and antibiotic resistance of respiratory bacteria in these two PCV7-vaccinated populations.MethodsIndigenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 29 publications
2
30
0
1
Order By: Relevance
“…Importantly, patients receiving AZM were less likely to become colonized with respiratory pathogens but also were more likely to become colonized with macrolide-resistant microorganisms (32). In agreement with this notion, longitudinal studies of nasopharyngeal carriage of respiratory bacteria in indigenous Australian and Alaskan native children with bronchiectasis revealed that macrolide resistance was higher in Australian children, who received more AZM, than in Alaskan children (34).…”
Section: N Ontypeable (Noncapsulated) Haemophilus Influenzae (Nthi)mentioning
confidence: 69%
See 1 more Smart Citation
“…Importantly, patients receiving AZM were less likely to become colonized with respiratory pathogens but also were more likely to become colonized with macrolide-resistant microorganisms (32). In agreement with this notion, longitudinal studies of nasopharyngeal carriage of respiratory bacteria in indigenous Australian and Alaskan native children with bronchiectasis revealed that macrolide resistance was higher in Australian children, who received more AZM, than in Alaskan children (34).…”
Section: N Ontypeable (Noncapsulated) Haemophilus Influenzae (Nthi)mentioning
confidence: 69%
“…Several clinical studies have examined their potential for AECOPD prevention (32)(33)(34)(35)(36)(37). In particular, long-term prophylaxis with AZM in patients with moderate to severe COPD has been associated with a significantly decreased number of exacerbations and an improved quality of life.…”
Section: N Ontypeable (Noncapsulated) Haemophilus Influenzae (Nthi)mentioning
confidence: 99%
“…2,3 Haemophilus influenzae is commonly susceptible to macrolides but resistance rates of 3-15% have been reported in Aboriginal and Torres Strait Islander children. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Th e baseline clinical and socioeconomic features and upper airway microbiology of this group have been published previously. 13,14 Th e purpose of this report is to (1) characterize the pattern of AREs in this cohort of children over at least 3 years of observation and (2) identify clinical features that increased the risk of recurrent and severe AREs requiring hospitalization.…”
mentioning
confidence: 99%